Diversifikasi Olahan Sidat menjadi Produk Unagi Pastry - Khoeruddin Wittriansyah; Ari Kristiningsih (Universitas Djuanda, 2023)
Eel has a high nutritional content. The process of processing fillets and making kabayaki leaves waste eel fish bones. There are not many variations of processed eel and there is potential for using eel bones, so diversification efforts need to be made. This study aims to make processed pastry using bone flour and eel meat. Pastry dough made from wheat flour is added with eel flour, and eel meat with 3 variables; P1, P2, and P3. P1 was (5% bone flour and 25% eel meat), P2 was (7.5% bone flour and 30% eel meat) and P3 was (10% bone flour and 35% eel meat). Bone flour and eel meat were analyzed proximately to determine their nutritional content. Hedonic organoleptic analysis including taste, aroma, texture, and appearance was carried out on unagi pastry P1, P2, and P3. The results showed that the eel bones contained a high protein, (31.82%) and a low water content (3.37%). Eel meat contains 41.72% protein and 15.98% crude fat. Organoleptic results showed the panelists preferred Unagi Pastry P1 both in terms of taste (3.48), aroma (3.46), texture (3.42), and appearance (3.92).